Pelaksanaan Program Parenting di Pendidikan Anak Usia Dini - Lili Mulyani; Andika Dirsa; Soraya Rosna Samta (Universitas Ivet, 2023)
Knowledge of parenting is indispensable for teachers in Early Childhood Education. Children need the right stimulation so that their full potential can be developed as much as possible. Therefore, the Parenting Program organized by the Early Childhood Education Institution (PAUD) takes a very important role. This study was conducted to explain how is the implementation of the parenting program in one of Early Childhood Education or PAUD in Pagerbarang District, Tegal Regency, Central Java. A qualitative approach with descriptive method is used in this study. The results showed that the Parenting Program at PAUD namely as Miss Lily was as follows: 1) Parenting Seminar; 2) Visit My Home; 3) Family Gathering; 4) Field Trip; 5) Parent Gathering; 6) Counselling; 7) Cooking Class; 8) Market Days; 9) Volunteering; 10) Miss Lily Education Creativity Festival (GKMLE); and 11) Study Tour. The conclusion is that these programs are programmed by the school in one year of the academic calendar. These programs can also increase parents' knowledge about the best parenting for their children, increase parental involvement in school activities, and improve aspects of child development.